An Examination of the Listing of Analyst Coverage on Corporate Websites - Bradshaw, Mark T.; Lee, Lian Fen; Peterson, Kyle (The Accounting Review, 2024)
ABSTRACT We examine firm decisions to provide listings of sell-side analyst coverage on corporate investor relations (IR) websites. These listings are related to three major areas of financial research—voluntary disclosure, investor relations, and analysts. Our hand-collected data permit cross-sectional and time-series analyses. Firms are more likely to have such listings when analysts are more important information intermediaries and when firms are directly involved in managing their IR websites. For firms with listings, the probability of an analyst being included on the listing is increasing in firm awareness of and familiarity with the analyst, how active and favorable the analyst is, and the analyst’s reputation. Additional analysis indicates similar results across self-hosting versus third-party hosting IR websites, with a notable exception that self-hosting firms exhibit a stronger preference for analysts who issue more favorable research about the firm. Decisions to add or drop analysts from listings reinforce the main results. Data Availability: Data are available from public sources identified in the text. JEL Classifications: G17; G24; M41.